Dopamine D2Rs coordinate cue-evoked changes in striatal acetylcholine levels - Martyniuk, Kelly M. (2022)
In the striatum, acetylcholine (ACh) neuron activity is modulated co-incident with dopamine (DA) release in response to unpredicted rewards and reward-predicting cues and both neuromodulators are thought to regulate each other. While this co-regulation has been studied using stimulation studies, the existence of this mutual regulation in vivo during natural behavior is still largely unexplored. One long-standing controversy has been whether striatal DA is responsible for the induction of the cholinergic pause or whether DA D2 receptors (D2Rs) modulate a pause that is induced by other mechanisms. Here, we used genetically encoded sensors in combination with pharmacological and genetic inactivation of D2Rs from cholinergic interneurons (CINs) to simultaneously measure ACh and DA levels after CIN D2R inactivation in mice. We found that CIN D2Rs are not necessary for the initiation of cue-induced decrease in ACh levels. Rather, they prolong the duration of the decrease and inhibit ACh rebound levels. Notably, the change in cue-evoked ACh levels is not associated with altered cue-evoked DA release. Moreover, D2R inactivation strongly decreased the temporal correlation between DA and ACh signals not only at cue presentation but also during the intertrial interval pointing to a general mechanism by which D2Rs coordinate both signals. At the behavioral level D2R antagonism increased the latency to lever press, which was not observed in CIN-selective D2R knock out mice. Press latency correlated with the cue-evoked decrease in ACh levels and artificial inhibition of CINs revealed that longer inhibition shortens the latency to press compared to shorter inhibition. This supports a role of the ACh signal and it´s regulation by D2Rs in the motivation to initiate actions.